Mineralogical Composition of the Urinary Stones from Different Provinces in Iraq - Adnan H. Afaj; Meitham A. Sultan (The Scientific World Journal, 2005)
For this study, 25 samples of urinary stones were chosen from different provinces in Iraq as representative sampling localities. These samples of urinary stones were collected to represent kidney, urate, and bladder stones. The main objectives of this study are to try to shed some light on the possibilities of tracking down the effective environmental factors that determine the mineralogical and chemical composition of these stones. The stones were examined using several techniques, the most important of which was the use of the X-ray diffraction (XRD) technique to determine the mineralogical composition of these stones. A scanning electron microscopy (SEM) test was conducted to determine the crystallographic forms and structures for the minerals forming these stones. Optical properties of these minerals were studied using a polarizing microscope. All these techniques revealed that the calcium oxalate, represented in Whewellite mineral, is the most dominant type of these stones, in addition to other minerals such as Hydroxy apatite, Struvite, and Uricite. Dittmarite was pointed out for the first time ever in some samples. This mineral has not been determined in any previous study worldwide.Considering the results of mineralogical and chemical examinations of the urinary stones in question, and the statistical information gathered from the Iraqi Health Ministry, statistical analyses were applied. The ratio of male-female cases in this study happened to be 4:1, which was higher than the ratio in the years 1988–1989 and 1993–1994, 2:1; 3:1 respectively. The highest percentage of the cases was in the 15–50 age group, which is considered as the most productive years of human lifetime. This study showed that one of the most significant factors was that the mineralogical variation of urinary stones in some Iraqi provinces was due to geographical differences, which reflect the variation in lithogenic factors and also climatological factors. Other factors may be socioeconomic, genetic, physiological, and pathological, which remain the important factors in forming urinary stones.